Characteristics of Myeloid Differentiation and Maturation Pathway Derived from Human Hematopoietic Stem Cells Exposed to Different Linear Energy Transfer Radiation Types - Monzen, Satoru (Public Library of Science, 2013)
Exposure of hematopoietic stem/progenitor cells (HSPCs) to ionizing radiation causes a marked suppression of mature functional blood cell production in a linear energy transfer (LET)- and/or dose-dependent manner. However, little information about LET effects on the proliferation and differentiation of HSPCs has been reported. With the aim of characterizing the effects of different types of LET radiations on human myeloid hematopoiesis, in vitro hematopoiesis in Human CD34(+) cells exposed to carbon-ion beams or X-rays was compared. Highly purified CD34(+) cells exposed to each form of radiation were plated onto semi-solid culture for a myeloid progenitor assay. The surviving fractions of total myeloid progenitors, colony-forming cells (CFC), exposed to carbon-ion beams were significantly lower than of those exposed to X-rays, indicating that CFCs are more sensitive to carbon-ion beams (D (0) = 0.65) than to X-rays (D (0) = 1.07). Similar sensitivities were observed in granulocyte-macrophage and erythroid progenitors, respectively. However, the sensitivities of mixed-type progenitors to both radiation types were similar. In liquid culture for 14 days, no significant difference in total numbers of mononuclear cells was observed between non-irradiated control culture and cells exposed to 0.5 Gy X-rays, whereas 0.5 Gy carbon-ion beams suppressed cell proliferation to 4.9% of the control, a level similar to that for cells exposed to 1.5 Gy X-rays. Cell surface antigens associated with terminal maturation, such as CD13, CD14, and CD15, on harvest from the culture of X-ray-exposed cells were almost the same as those from the non-irradiated control culture. X-rays increased the CD235a(+) erythroid-related fraction, whereas carbon-ion beams increased the CD34(+)CD38(−) primitive cell fraction and the CD13(+)CD14(+/−)CD15(−) fraction. These results suggest that carbon-ion beams inflict severe damage on the clonal growth of myeloid HSPCs, although the intensity of cell surface antigen expression by mature myeloid cells derived from HSPCs exposed to each type of radiation was similar to that by controls.